Prolong cryopreservation duration negatively affects pregnancy outcomes of vitrified-warmed blastocyst transfers using an open-device system: A retrospective cohort study. (February 2023) - Zheng, Qizhen; Mo, Meilan; Zhang, Hongzhan; Xu, Shiru; Xu, Fen; Wang, Sisi; Zeng, Yong
Abstract: Objective: To investigate the impact of cryopreservation (CP) duration on pregnancy outcomes of vitrified-warmed blastocysts transfers using an open-device liquid-nitrogen (LN2 ) system. Methods: This retrospective cohort study was conducted on 6327 first vitrified-warmed single blastocyst transfer cycles with autologous oocytes from January 2015 to December 2020. The CP duration was initially divided into six groups: Group I: 0–3 months (n = 4309); Group II: 4–6 months (n = 1061); Group III: 7–12 months (n = 304); Group IV: 13–24 months (n = 113); Group V: 25–72 months (n = 466); Group VI: 73–120 months (n = 74). Multivariate logistic regression was performed to evaluate the independent effect of CP duration on pregnancy outcomes. To further examine the time limit of vitrification, propensity score matching (PSM) was applied to compare pregnancy outcome of patients with storage duration of 25–120 months to those of 0–24 months. After that, pregnancy outcomes were compared among the subgroups of Group I': 0–24 months, Group II': 25–48 months, Group III': 49–72 months, Group IV': 73–120 months. Stratification analysis based on embryo quality was also performed. Primary outcomes were clinical pregnancy rate and live birth rate. Secondary outcomes were implantation, biochemical pregnancy rate, ongoing pregnancy rate and early miscarriage rate. Results: Logistic regression demonstrated that the odds of pregnancy outcomes were similar across Group I to IV. However, the implantation rate, chances of biochemical pregnancy, clinical pregnancy, ongoing pregnancy, and live birth significantly decreased as the storage duration increased up to 25 months, while miscarriage rate did not significantly differ between groups. Subgroup analysis confirmed a dramatical decrease of clinical pregnancy and live birth rate when cryopreserved for more than 24 months. After that, the slope was relatively steady between 25 and 72 months, then steeply decreased again as CP reached 73–120 months. In addition, there was a more remarkable decline of pregnancy outcomes in the average quality embryo transfers than in the high quality embryo transfers as cryopreservation storage increased. Conclusion: Prolonged cryopreservation of vitrified blastocysts in an open-device LN2 system up to 24 months might negatively affect pregnancy outcomes. This negative impact progresses as storage duration increases, especially when exceeds 72 months. Average quality embryo appears to be less sustainable with long-term cryo-storage.